FINANCIAL SECURITY OF THE STOCK EXCHANGE MARKET IN THE SYSTEM OF FINANCIAL SECURITY OF THE STATE - Holovach, M. (Socio-economic relations in the digital society, 2021)
The article examines the role of the stock exchange market in ensuring the financial security of theState, its integration into the world economic space. The main focus of the article was concentrated on thedomestic government bond market, as this stock exchange market accounts for 95% of the total stock exchangemarket in Ukraine. Have been proved the necessity of studying the financial security of the domestic governmentbond market. Emphasis is placed on the connection of financial security of the stock exchange market withinvestment, debt security of the state and financial security of legal entities and individuals. The approachesproposed to determine the issue of financial security of the stock exchange market and its external and internalcomponents are considered. Also, I analyzed external and internal threats that may affect the securities marketin Ukraine. The data of the primary and secondary market of domestic government bonds and fluctuationsof the hryvnia exchange rate against foreign currencies were studied. An analyzed the relationship betweenthe obtained data on the markets of primary placement of domestic government bonds, their secondary saleand exchange rate fluctuations of the hryvnia against the US dollar over a two-month period and negativeexternal factors on the financial security of stock exchange in this range. Have been made an assessment of thefinancial security of the domestic government bond market from external factors in Ukraine. Have been studiedthe probable negative scenarios that would have an impact on the national economy in the event of repeated or continuous action of these negative external factors on the domestic government bond market. Have beenclarified which subjects need to pay more attention to the issue raised in the article and suggested in whichdirection the Ministry of Finance of Ukraine, the National Bank of Ukraine and scientists should cooperate.
Keywords: financial markets; stock exchange market; the financial security of the stock exchange market; the economic security of the securities market; negative factors on the securities market